Implications of the Accuracy of MEPS Prescription Drug Data for Health Services Research - Steven C. Hill; Samuel H. Zuvekas; Marc W. Zodet (SAGE Publishing, 2011)
This paper assesses the quality of the Medical Expenditure Panel Survey (MEPS) drug data and the impact that misreporting prescription drug data has on descriptive and behavioral analyses. It does this by matching MEPS participants with Medicare Part D coverage during the period 2006-2007 to their Part D claims data. In the validation sample, the number of drug fills and total expenditures are reasonably accurate compared with claims. Household respondents tended to underreport the number of different drugs taken, but tended to overreport the number of fills of each drug. Behavioral analyses of the determinants of medication use and expenditures were largely unaffected because underreporting cut across most sociodemographic groups.